Modified an Automatic-Cleaning Strainer for Seawater Cooling System in Combined Cycle Power Plant - Okwaldu Purba; Erryawan Kusuma; Ferdiansyah Zhultriza; Riza Kurniawan (Department of Electrical Engineering ITS and FORTEI, 2025)
The power plant industries on the coast use seawater as a cooling water system. Seawater conditions in densely populated areas, such as Jakarta, have high levels of pollutants which can affect cooling water systems. To filter seawater from pollutants, a strainer is used due to reliability must be maintained. This research is located at a power plant in North Jakarta. This research describes the latest proposed design of an automatic-cleaning strainer that poses less risk to the system and is faster in the work process. The results of this design were implemented at the generating company. This design can maintain strainer reliability with a faster strainer cleaning process, which reduces the TTR (Time to Repair) in the generating unit from 3 hours to 5 minutes, with no risk of damage to the system due to foreign material in the cooling water system. In addition, the results of this research help improve plant operation and maintenance performance, by increasing EAF 1.11%, increasing 1 level in Maintenance Mix Cost and Manhour from Level 4 to Level 5, increasing Reliability Management by 0.1 level, and also reducing EFOR by 0.98%. Work processes that are carried out automatically via smartphones also contribute to the digitization of the power generation industry to make it more effective and efficient.